Analisis Sikap, Norma Subyektif, Faktor Internal Dan Eskternal Dalam Membentuk Entrepreneurial Intentions - Dian Triyani; Ardiani Ika Sulistyawati; Edy Mulyantomo (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to analyze the influence of attitudes, subjective norms, internal and external factors on entrepreneurial intentions. The research object of the Faculty of Economics, University of Semarang with the analysis unit of students of the Faculty of Economics, University of Semarang who is still an active status. The type of data needed in this study is primary data that comes from the answers of the respondents to the questionnaires that were distributed. The results showed that attitudes, subjective norms, internal factors and external factors had a positive and significant effect on intrapreneurial Intentions. The results of this study are only able to explain intrapreneurial Intentions only 35.8% and the remaining 64.2% are explained by other variables.